Genome editing to reveal peptidergic heterogeneity of POMC neurons regulating energy and glucose balance - Low, Cho. (2018)
Abstract: Diabetes is a global health concern that has dire consequences if left unchecked. However, the pathogenesis of diabetes is still not completely understood and so effective treatments are lacking. Growing evidence has shown that neurons in the brain, particularly those in the hypothalamus, play an important role in regulating whole body blood glucose, and that their dysfunctions contribute to the development of diabetes. However, the complexity of the neural system, and difficulties in probing neuronal functions in vivo, have left us with an incomplete understanding of both the molecular mechanism and neuro-circuitry of centralized blood glucose regulation. In our recent study, we have perturbed a major group of glucose-sensing neurons in the hypothalamus, Pro-opiomelancortin (POMC) neurons in the arcuate nucleus (ARC). We observed that these groups of neurons play a significant role in regulating whole body glucose homeostasis. Here we on POMC neurons and utilize a battery of genetic approaches to securitized the machinery operating within them. Briefly, using a chemogenetic approach with both cell type and brain region specificity to acutely manipulate the firing of these neurons, we observed that these neurons directly regulate energy expenditure, locomotion and blood glucose levels. Utilizing novel CRISPR technology in vivo, we specifically ablated POMC in the ARC. We found that POMC is necessary for energy and locomotor homeostasis, but has only a secondary effect on glucose levels. Thus, we hypothesize that another key neuropeptide found in POMC neurons, cocaine amphetamine regulated transcript (CART) may control glucose homeostasis. Using a similar approach, we show that CART is necessary to maintain blood glucose levels and that its depletion in Type 1 diabetes (T1D) and Type 2 diabetes (T2D) mouse models contributes to the development of hyperglycemia. Finally, using an unbiased approach and terminal inhibition we conclude that the paraventricular nucleus of the hypothalamus (PVH) is the main downstream glucoregulatory target. Collectively, these findings provide direct evidence to the underlying molecular mechanisms of POMC neuronal activity and the neural circuits used to employ them. Our study has provided novel insight into brain-regulated glucose homeostasis and has identified potential targets for treating and preventing diabetes.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisors: Dong Kong, and Maribel Rios.; Committee: Daniel Jay, Leon Reijmers, and Peng Yi.; Keyword: Neurosciences.